Sistem Kontrol Telemetri Banjir di Kelurahan Belian Batam - Torong, Helpi; Mardiono, Djoko Anwar; Apriyanto, Bambang; Friadi, John (Penerbit Goodwood, 2023)
Purpose: The design of this flood telemetry control system aims to determine the water level in the drainage and provide warnings of potential flooding to the public with direct notifications to applications running on Android smartphones and to reduce the impact of flooding, a flood detection system tool was built using sensors that connected to a microcontroller that will detect the water level. Methodology: The design of this tool uses 3 (three) sources of information that are installed separately far apart, namely locations A, B, and C connected via the internet network and provide information in the form of monitoring, direct warnings to applications installed on Android Smart Phones. Result: The results of testing this tool work well. And can find out the water level when the rainy season arrives in the environment around the residence from a distance. This tool provides notifications with a delay of about ± 1000ms or 1 second at the smartphone internet access speed to the teleduino webserver or vice versa ± 142ms.